Paradoxical Positioning: Does "Head Up" Always Improve Mechanics and Lung Protection?*. Issue 11 (21st July 2022) - Selickman, John; Crooke, Philip S.; Tawfik, Pierre; Dries, David J.; Gattinoni, Luciano; Marini, John J.
Abstract : OBJECTIVES: Head-elevated body positioning, a default clinical practice, predictably increases end-expiratory transpulmonary pressure and aerated lung volume. In acute respiratory distress syndrome (ARDS), however, the net effect of such vertical inclination on tidal mechanics depends upon whether lung recruitment or overdistension predominates. We hypothesized that in moderate to severe ARDS, bed inclination toward vertical unloads the chest wall but adversely affects overall respiratory system compliance (Crs ). DESIGN: Prospective physiologic study. SETTING: Two medical ICUs in the United States. PATIENTS: Seventeen patients with ARDS, predominantly moderate to severe. INTERVENTION: Patients were ventilated passively by volume control. We measured airway pressures at baseline (noninclined) and following bed inclination toward vertical by an additional 15°. At baseline and following inclination, we manually loaded the chest wall to determine if Crs increased or paradoxically declined, suggestive of end-tidal overdistension. MEASUREMENTS AND MAIN RESULTS: Inclination resulted in a higher plateau pressure (supineΔ: 2.8 ± 3.3 cm H2 O [ p = 0.01]; proneΔ: 3.3 ± 2.5 cm H2 O [ p = 0.004]), higher driving pressure (supineΔ: 2.9 ± 3.3 cm H2 O [ p = 0.01]; proneΔ: 3.3 ± 2.8 cm H2 O [ p = 0.007]), and lower Crs (supine Δ: 3.4 ± 3.7 mL/cm H2 O [ p = 0.01]; proneΔ: 3.1 ± 3.2 mL/cm H2 O [ p = 0.02]). Following inclination, manual loading of the chest wall restored Crs and driving pressure to baseline (preinclination) values. CONCLUSIONS: In advanced ARDS, bed inclination toward vertical adversely affects Crs and therefore affects the numerical values for plateau and driving tidal pressures commonly targeted in lung protective strategies. These changes are fully reversed with manual loading of the chest wall, suggestive of end-tidal overdistension in the upright position. Body inclination should be considered a modifiable determinant of transpulmonary pressure and lung protection, directionally similar to tidal volume and positive end-expiratory pressure.